Dasar–Dasar Keyakinan Kristen Yang Terkait Dengan Proses PAK - Kezia Almanda Oni Eki (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2023)
This article discusses how to become a PAK teacher who lives by adhering to the basics of the Christian Faith as the basis of our Christian Faith is God. The life of a PAK teacher must always have a close relationship with God through praise, worship, and personal fellowship with Him. PAK teachers must be able to be role models for students like Jesus who is an example for our lives. In Hebrews 11: 1 it is said that "Faith is the basis of everything we hope for and the evidence of everything we do not see", faith is very necessary in the teaching of PAK, otherwise he cannot teach well to children because of Faith to Jesus Christ is the basis and example for a PAK teacher. The goal of a PAK teacher's teaching is to bring children to true faith in Christ and live in truth. For example, Jesus had the ultimate goal of His teaching, namely repentance and renewal of life.